The Impact of Overseas Training on the Performance of Bangladesh Civil Service: The Case of AIT Extension Training, Thailand - Mohammad Ali Haider; Shamim Noor (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2021)
Public administration has to compete with private sectors in terms of quality service delivery to citizens. In this context, civil service training, especially overseas training, has been considered the most significant requirement to increase the performance of the Bangladesh Civil Service. This article tries to explore the impact of overseas training on the performance of the Bangladesh Civil Service. To achieve this objective, this study interviewed Bangladesh Civil Servants who participated Asian Institute Training (AIT) Extension training programme from 2016 to 2018. A mixed-method was applied to analyse the collected data. It found that Bangladesh Civil Servants, who have received AIT Extension training, were satisfied with the training management of AIT. Participants believed that such overseas training positively contributes to enhancing the performance of the Bangladesh Civil Service. However, this study also disclosed that fewer overseas training opportunities for young civil servants, lack of need-based training, and poor management of overseas training policy are the main obstacles in Bangladesh Civil service management. This article strongly recommends that there must be a detailed overseas training policy management and more collaboration with international training institutes to get better performance from the government officers in Bangladesh.